A retrospective study of relationship between white blood cell counts in cervical discharge and Chlamydial cervicitis among young adults: is the simple microscope an alternative method for diagnosing the disease? - Arunothong, Surachet; Yasamut, Wisanukorn; Chetacha, Nilawan; Somrit, Jenjira; Putthawong, Pornpilin (Biomedical Sciences and Clinical Medicine, 2023)
Objectives This retrospective study aimed to examine the relationship between white blood cell counts and Chalmydial infection of the uterine cervix among young adults in the STI Clinic, Office of Disease Prevention and Control, region 10 Chiang Mai. Methods Two hundred and twenty women, who were aged less than 25 years and attended the STI clinic in 2011 Fiscal year, had their cervical discharge collected and examined in the laboratory by microscopic examination (gram stain) and the In-house PCR Chlamydia test, which already compared to a standard commercial method. The result of the In-house PCR Chlamydia test was acceptable at 95 percent confident interval. The target population was classified into two groups: sex workers (140 people) and non-sex workers (80 people). The white blood cell count in their cervical discharge and the result of the In-house PCR Chlamydia test were examined via Chi-Square tests for a significant correlation in each group. Results A significant correlation between white blood cell count in cervical discharge and Chlamydial cervicitis was presented in the sex worker group; with the cutoff point of the leukocyte count being ≥5 cells/1,000X microscopic power field (p value: < 0.001). Sensitivity of the “white blood cell” gave a positive diagnostic result for Chlamydial cervicitis (at least 5 cells/1,000X microscopic power field) in 74.29 percent of the sex worker group with 72.38 percent specifiity. In contrast, there was no significant relationship between the white blood cell count in cervical discharge and Chlamydial cervicitis among the non-sex worker group. Sensitivity of the “white blood cell” gave a positive diagnostic result for Chlamydial cervicitis (at least 5 cells/1,000X microscopic power field) in 79.17 percent of the non-sex worker group with 41.07 percent specificity. Conclusions The white blood cell count criterion of ≥5 cells/1,000X microscopic power field in a cervical smear provides an alternative diagnostic method for Chlamydial cervicitis detection in sex workers aged less than 25 years.